Eksistensi Lembaga Pendidikan Pesantren Salaf Ditengah Arus Modernitas - SUBRI SUBRI (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
The existence of Salaf Islamic boarding schools must follow developments and modernization in every aspect of its development. Salaf Islamic boarding schools must open themselves from the rapid progress and development of the outside world and must be able to understand their needs and demands. The existence of the Salaf Islamic boarding school Nurul Muhibbin in Kemuja Village certainly must be able to color the stage of modernity to face the global challenges of the outside world, must be able to adapt and interact by not leaving and eliminating the values of salafiyah purity in accepting the development activities of the times. Of course, too, modernity has many advantages, but besides that there are also many possibilities that must be avoided. Progress in the field of technology must be watched out by Islamic boarding schools in general, the rapid development of technology should not then make the collapse of the pure values of Islamic teachings in salaf boarding schools just the opposite how Salaf Islamic boarding schools can use this information technology as a means to develop and promote education and teaching in Islamic boarding schools.